Potential distribution and conservation of the Colobosauroides carvalhoi Soares and Caramaschi, 1998: a rare and endemic lizard of Northeast Brazil - Magalhães-Júnior,A. J. C. (2017)
Abstract Ecological niche modeling has contributed to the investigation of the geographical distribution and conservation of rare or little recorded species. Therefore, we studied the known and potential distributions of Colobosauroides carvalhoi Soares and Caramaschi 1998 and discuss the implications for its conservation. Data were obtained by manual collections made in quarterly samplings in three different regions, considering the regions with occurrence records and surrounding areas. The known distribution was determined by occurrence records and literature data, and potential distribution was estimated with an ecological niche model by the MaxEnt algorithm. Twenty-five specimens were collected exclusively in forest formations of Caatinga and Caatinga-Cerrado. Our data corroborated the relative rarity of C. carvalhoi and reflected the biogeographical history of the group, where it is restricted to forest formations with milder environmental conditions. The occurrence records indicated new records of C. carvalhoi, but the known distribution value is compatible with a restricted distribution. The ecological niche model estimated few areas with environmental suitability for the species and corroborated the restricted and relict distribution patterns. Finally, the known and potential distribution values ​​were compatible with criteria for threatened species. These results suggest a worrisome scenario for C. carvalhoi conservation. However, the limited data about the species population do not allow the proper definition of its conservation status. Therefore, we suggest using potential distribution values with alternative criteria for redefining the conservation status of C. carvalhoi and the development of new studies that support a better assessment of its conservation aspects.